The impact of hormonal changes and motivation during the menstrual cycle on women’s appetite and craving - Mohd Nasir, Azira; Muhamad Firdaus, Muhamad Iman Al-Furqan; Abd Razak, Iylia Batrisyia; Nur’adzan Fadzil Akbar, Nur Afifah; Azrell, Nur Erisha; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Alaa Eldin, Amirah Hannan; Md Tajudin, Huriyyah Hamiemah; Jaffer, Usman (Global Academic Excellence (GAE), 2025)
This paper explores the interplay between hormonal fluctuations during the menstrual cycle and their impact on women's appetite, cravings, and emotional well-being. A comprehensive review of the literature reveals consistent findings that hormonal changes, particularly in serotonin and insulin levels, are positively correlated with variations in motivation, cravings, and mood across the menstrual phases. The luteal phase (LP), characterized by a drop in serotonin, is associated with heightened carbohydrate cravings and mood swings. This review synthesizes evidence highlighting the role of nutrient-dense, personalized dietary interventions in mitigating these effects, including the consumption of protein-rich meals to reduce emotional eating and depressive symptoms. Additionally, mindfulness practices and regular physical activity emerge as effective strategies for managing hormonal imbalances by reducing stress, enhancing mood, and promoting self-control. To address the identified challenges, this paper proposes practical applications such as education on hormonal fluctuations, tailored nutrition plans, and the integration of mindfulness and exercise into daily routines. Furthermore, it emphasizes the importance of cultural and lifestyle considerations in shaping dietary behaviors during the menstrual cycle. From an Islamic perspective, the teachings of moderation and mindfulness, as well as spiritual practices such as dhikr and reciting Surah Al-Fatiha, offer additional support in managing hormonal changes and promoting balance. Future research is recommended to explore sociocultural influences, lifestyle variations, and long-term interventions, offering a holistic approach to managing menstrual-related changes.